1,2-Naphthoquinone-4-sulfonic acid salts in organic synthesis - Ribeiro, Ruan Carlos B.; Ferreira, Patricia G.; Borges, Amanda de A.; Forezi, Luana da S. M.; da Silva, Fernando de Carvalho; Ferreira, Vitor F. (Beilstein Journal of Organic Chemistry, 2022)
Several low molecular weight naphthoquinones are very useful in organic synthesis. These compounds have given rise to thousands of other naphthoquinones that have been tested against various microorganisms and pharmacological targets, including being used in the preparation of several drugs that are on the pharmaceutical market. Among these naphthoquinones, the series of compounds prepared from 1,2-naphthoquinone-4-sulfonic acid salts (β-NQS) stands out. In addition to being used in organic synthesis, they are excellent analytical derivatization reagents to spectrophotometrically determine drugs containing primary and secondary amino groups. This review summarizes the literature involving β-NQS.
Keywords: biological activities; derivatization reagents; β-NQS; organic synthesis

Naturally Occurring Quinones IV - Thomson, R. H. (Blackie Acad. and Professional, 1997)

(untitled) - O’Brien, P. J. (Chem.-Biol. Interact., 1991)

(untitled) - Powis, G. (Pharmacol. Ther., 1987)

(untitled) - Rinehart, K. L., Jr; Shield, L. S. (Fortschr. Chem. Org. Naturst., 1976)

(untitled) - Santos, L. O.; dos Anjos, J. P.; Ferreira, S. L. C.; de Andrade, J. B. (Microchem. J., 2017)

(untitled) - Sousa, E. T.; Lopes, W. A.; de Andrade, J. B. (Quim. Nova, 2016)

(untitled) - Pereyra, C. E.; Dantas, R. F.; Ferreira, S. B.; Gomes, L. P.; Silva-Jr, F. P. (Cancer Cell Int., 2019)

(untitled) - Qiu, H.-Y.; Wang, P.-F.; Lin, H.-Y.; Tang, C.-Y.; Zhu, H.-L.; Yang, Y.-H. (Chem. Biol. Drug Des., 2018)

(untitled) - Varghese, K. J.; Silvipriya, K. S.; Resmi, S.; Jolly, C. I. (Inventi Impact: Cosmeceuticals, 2010)

(untitled) - Saeed, S. M. G.; Sayeed, S. A.; Ashraf, S.; Naz, S.; Siddiqi, R.; Ali, R.; Mesaik, M. A. (Pak. J. Bot., 2013)

(untitled) - Yusuf, M.; Ahmad, A.; Shahid, M.; Khan, M. I.; Khan, S. A.; Manzoor, N.; Mohammad, F. (J. Cleaner Prod., 2012)

(untitled) - de Paiva, S. R.; Lima, L. A.; Figueiredo, M. R.; Kaplan, M. A. C. (An. Acad. Bras. Cienc., 2004)

(untitled) - de Carvalho da Silva, F.; Francisco Ferreira, V. (Curr. Org. Synth., 2016)

(untitled) - Liao, C.-C.; Peddinti, R. K. (Sci. Synth., 2006)

(untitled) - Chaudhary, A.; Khurana, J. M. (Curr. Org. Chem., 2016)

(untitled) - López, L. I. L.; Flores, S. D. N.; Belmares, S. Y. S.; Galindo, A. S. (Vitae, 2014)

(untitled) - Sartori, M. F. (Chem. Rev., 1963)

(untitled) - Badave, K. D.; Khan, A. A.; Rane, S. Y. (Anti-Cancer Agents Med. Chem., 2016)

(untitled) - Padhye, S.; Dandawate, P.; Yusufi, M.; Ahmad, A.; Sarkar, F. H. (Med. Res. Rev., 2012)

(untitled) - Lamoureux, G.; Perez, A. L.; Araya, M.; Agüero, C. (J. Phys. Org. Chem., 2008)

(untitled) - Sharma, A.; Santos, I. O.; Gaur, P.; Ferreira, V. F.; Garcia, C. R. S.; da Rocha, D. R. (Eur. J. Med. Chem., 2013)

(untitled) - García-Barrantes, P. M.; Lamoureux, G. V.; Pérez, A. L.; García-Sánchez, R. N.; Martínez, A. R.; San Feliciano, A. (Eur. J. Med. Chem., 2013)

(untitled) - Lezama-Dávila, C. M.; Isaac-Márquez, A. P.; Kapadia, G.; Owens, K.; Oghumu, S.; Beverley, S.; Satoskar, A. R. (Biol. Pharm. Bull., 2012)

(untitled) - Asche, C. (Mini-Rev. Med. Chem., 2005)

(untitled) - Baell, J. B.; Nissink, J. W. M. (ACS Chem. Biol., 2018)

(untitled) - Aldrich, C.; Bertozzi, C.; Georg, G. I.; Kiessling, L.; Lindsley, C.; Liotta, D.; Merz, K. M., Jr; Schepartz, A.; Wang, S. (ACS Med. Chem. Lett., 2017)

The Vitamins - Combs, G. F., Jr; McClung, J. P. (Vitamin K, 2017)

(untitled) - Olliaro, P.; Wirth, D. (J. Pharm. Pharmacol., 1997)

(untitled) - França, T. C. C.; dos Santos, M. G.; Figueroa-Villar, J. D. (Quim. Nova, 2008)

(untitled) - Watts, J.; Playford, M.; Hickey, K. N. Z. (Vet. J., 2016)

(untitled) - Dobbelaere, D.; Heussler, V. (Annu. Rev. Microbiol., 1999)

(untitled) - Mhadhbi, M.; Naouach, A.; Boumiza, A.; Chaabani, M. F.; BenAbderazzak, S.; Darghouth, M. A. (Vet. Parasitol., 2010)

(untitled) - Sharifiyazdi, H.; Namazi, F.; Oryan, A.; Shahriari, R.; Razavi, M. (Vet. Parasitol., 2012)

(untitled) - Hashemi-Fesharki, R. (Res. Vet. Sci., 1991)

(untitled) - Garnier, T.; Mantyla, A.; Jarvinen, T.; Lawrence, J.; Brown, M.; Croft, S. (J. Antimicrob. Chemother., 2007)

(untitled) - Hawa, N.; Rae, D. G.; Younis, S.; Mahadi, W.; Ibrahim, R.; Al-Wahab, W. (Trop. Anim. Health Prod., 1988)

(untitled) - Ferreira, V. F.; Ferreira, S. B.; de Carvalho da Silva, F. (Org. Biomol. Chem., 2010)

(untitled) - da Rocha, D. R.; de Souza, A. C. G.; Resende, J. A. L. C.; Santos, W. C.; dos Santos, E. A.; Pessoa, C.; de Moraes, M. O.; Costa-Lotufo, L. V.; Montenegro, R. C.; Ferreira, V. F. (Org. Biomol. Chem., 2011)

(untitled) - Moreira, C. d. S.; Nicoletti, C. D.; Pinheiro, D. P.; de Moraes, L. G. C.; Futuro, D. O.; Ferreira, V. F.; Pessoa, C. d. Ó.; da Rocha, D. R. (Med. Chem. Res., 2019)

(untitled) - Pradhan, R.; Dandawate, P.; Vyas, A.; Padhye, S.; Biersack, B.; Schobert, R.; Ahmad, A.; Sarkar, F. H. (Curr. Drug Targets, 2012)

(untitled) - Gouda, M. A.; Eldien, H. F.; Girges, M. M.; Berghot, M. A. (Med. Chem., 2013)

(untitled) - Nakahara, Y.; Ishigami, A.; Takeda, Y. (J. Chromatogr. B: Biomed. Sci. Appl., 1989)

(untitled) - Witt, O. N. (Ber. Dtsch. Chem. Ges., 1891)

(untitled) - Böniger, M. (Ber. Dtsch. Chem. Ges., 1894)

(untitled) - Folin, O.; Wu, H. (J. Biol. Chem., 1922)

(untitled) - Obo, F. (J. Biochem., 1941)

(untitled) - Fu, B.; Liu, T.; Chen, J.; Li, K. (Sens. Actuators, B, 2018)

(untitled) - Danielson, I. S. (J. Biol. Chem., 1933)

(untitled) - Martin, E. L.; Fieser, L. F. (Org. Synth., 1941)

(untitled) - Gummadi, S.; Kommoju, M. (Am. J. PharmTech Res., 2019)

(untitled) - Adegoke, O. A. (Int. J. Pharm. Sci. Rev. Res., 2012)

(untitled) - Elbashir, A. A.; Ahmed, A. A.; Ali Ahmed, S. M.; Aboul-Enein, H. Y. (Appl. Spectrosc. Rev., 2012)

(untitled) - Hiyama, M. (Yakugaku Zasshi, 1952)

(untitled) - Hashimoto, Y.; Endo, M.; Tominaga, K.; Inuzuka, S.; Moriyasu, M. (Microchim. Acta, 1978)

(untitled) - Saurina, J.; Hernández-Cassuo, S. (Anal. Chim. Acta, 1993)

(untitled) - Legua, C. M.; Falcó, P. C.; Cabeza, A. S. (Anal. Chim. Acta, 1993)

(untitled) - Molins Legua, C.; Campins Falcó, P.; Sevillano Cabeza, A. (Fresenius' J. Anal. Chem., 1994)

(untitled) - Xu, L.; Wang, H.; Xiao, Y. (Spectrochim. Acta, Part A, 2004)

(untitled) - Kumar, C. H. A.; Kumar, T. A.; Gurupadayya, B. M.; Sloka, N.; Reddy, M. B. R. (Arch. Appl. Sci. Res., 2010)

(untitled) - Elbashir, A. A.; Elwagee, A. H. E. (J. Assoc. Arab Univ. Basic Appl. Sci., 2012)

(untitled) - Osman, R. A. M.; Elbashir, A. A. (Int. J. Bioanal. Methods Bioequival. Stud., 2019)

(untitled) - Khalil, N. A.; Ibrahim, W. H. (Tikrit J. Pure Sci., 2020)

(untitled) - Awan, Z. A.; Hegazy, M. A.; Kammoun, A. K. (Spectrochim. Acta, Part A, 2020)

(untitled) - Darwish, I. A.; Al-Shehri, M. M.; El-Gendy, M. A. (Chem. Cent. J., 2012)

(untitled) - Ahmed, S. M.; Elbashir, A. A. (J. Anal. Bioanal. Tech., 2015)

(untitled) - Altigani, A. M. N.; Elbashir, A. A. (Austin J. Anal. Pharm. Chem., 2014)

(untitled) - Abdulrahman, S. A. M.; Basavaiah, K. (Drug Test. Anal., 2011)

(untitled) - Elbashir, A. A.; Awad, S. F. J. (Pharmacovigilance, 2013)

(untitled) - Salman, B. I.; Hussein, S. A.; Ali, M. F. B.; Marzouq, M. A. (Microchem. J., 2019)

(untitled) - Hartke, K.; Lohmann, U. (Chem. Lett., 1983)

(untitled) - Fieser, L. F.; Fieser, M. (J. Am. Chem. Soc., 1935)

(untitled) - Yano, H.; Yamasaki, M.; Shimomura, Y.; Iwasaki, M.; Ohta, M.; Furuno, Y.; Kouno, K.; Onu, Y.; Ueda, Y. (Chem. Pharm. Bull., 1980)

(untitled) - Fieser, L. F.; Fieser, M. (J. Am. Chem. Soc., 1934)

(untitled) - Harmon, R. E.; Phipps, L. M.; Howell, J. A.; Gupta, S. K. (Tetrahedron, 1969)

(untitled) - Fernández, A. E.; De Bertorello, M. M.; Longhi, M. R. (J. Liq. Chromatogr., 1984)

(untitled) - Fragoso, T. P.; de Mesquita Carneiro, J. W.; Vargas, M. D. (J. Mol. Model., 2010)

(untitled) - Gornostaev, L. M.; Rukovets, T. A.; Lavrikova, T. I.; Khalyavina, Y. G.; Stashina, G. A. (Russ. Chem. Bull., 2017)

(untitled) - Gornostaev, L. M.; Rukovets, T. A.; Arnold, E. V.; Khalyavina, Y. G.; Gatilov, Y. V. (Russ. J. Org. Chem., 2018)

(untitled) - Ortiz, C. S.; Longhi, M. R.; De Bertorello, M. M.; Briñon, M. C. (Org. Prep. Proced. Int., 1991)

(untitled) - Khalil, A. M.; Berghot, M. A.; Gouda, M. A. (Eur. J. Med. Chem., 2010)

(untitled) - Gouda, M. A. (Arch. Pharm. (Weinheim, Ger.), 2012)

(untitled) - Ahn, J. H.; Cho, S. Y.; Ha, J. D.; Chu, S. Y.; Jung, S. H.; Jung, Y. S.; Baek, J. Y.; Choi, I. K.; Shin, E. Y.; Kang, S. K.; Kim, S. S.; Cheon, H. G.; et al. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Gouda, M. A.; Sherif, Y. E.-S.; Elsherbini, M. S. (Phosphorus, Sulfur Silicon Relat. Elem., 2014)

(untitled) - Hatfield, M. J.; Chen, J.; Fratt, E. M.; Chi, L.; Bollinger, J. C.; Binder, R. J.; Bowling, J.; Hyatt, J. L.; Scarborough, J.; Jeffries, C.; Potter, P. M. (J. Med. Chem., 2017)

(untitled) - Takizawa, Y.; Munakata, T.; Iwasa, Y.; Suzuki, T.; Mitsuhashi, T. (J. Org. Chem., 1985)

(untitled) - Yang, H.; An, B.; Li, X.; Zeng, W. (Bioorg. Med. Chem. Lett., 2018)

(untitled) - Carroll, F. I.; Miller, H. W.; Meck, R. (J. Chem. Soc. C, 1970)

(untitled) - Yamada, T.; Yamashita, T.; Nakamura, M.; Shimamura, H.; Yamaguchi, A.; Takaya, M. (Yakugaku Zasshi, 1980)

(untitled) - Moore, H. W.; Shelden, H. R.; Weyler, W., Jr (Tetrahedron Lett., 1969)

(untitled) - Campos, V. R.; dos Santos, E. A.; Ferreira, V. F.; Montenegro, R. C.; de Souza, M. C. B. V.; Costa-Lotufo, L. V.; de Moraes, M. O.; Regufe, A. K. P.; Jordão, A. K.; Pinto, A. C.; Resende, J. A. L. C.; Cunha, A. C. (RSC Adv., 2012)

(untitled) - Tseng, C.-H.; Cheng, C.-M.; Tzeng, C.-C.; Peng, S.-I.; Yang, C.-L.; Chen, Y.-L. (Bioorg. Med. Chem., 2013)

(untitled) - Almeida, R. G.; Valença, W. O.; Rosa, L. G.; de Simone, C. A.; de Castro, S. L.; Barbosa, J. M. C.; Pinheiro, D. P.; Paier, C. R. K.; de Carvalho, G. G. C.; Pessoa, C.; Goulart, M. O. F.; Kharma, A.; et al. (RSC Med. Chem., 2020)

(untitled) - Pinto, A. V.; Pinto, C. N.; Pinto, C. F. R.; Rita, R. S.; Pezzella, C. A. C.; Castro, S. L. (Arzneim. Forsch., 1997)

(untitled) - Chaves, J. P.; Pinto, M. d. C. F. R.; Pinto, A. V. (J. Braz. Chem. Soc., 1990)

(untitled) - Neves-Pinto, C.; Malta, V. R. S.; Pinto, M. d. C. F. R.; Santos, R. H. A.; de Castro, S. L.; Pinto, A. V. (J. Med. Chem., 2002)

(untitled) - de Moura, K. C. G.; Emery, F. S.; Neves-Pinto, C.; Pinto, M. d. C. F. R.; Dantas, A. P.; Salomão, K.; de Castro, S. L.; Pinto, A. V. (J. Braz. Chem. Soc., 2001)

(untitled) - Tseng, C.-H.; Lin, C.-K.; Chen, Y.-L.; Tseng, C.-K.; Lee, J.-Y.; Lee, J.-C. (Eur. J. Med. Chem., 2018)

(untitled) - Ooyama, Y.; Nonami, K.; Watanabe, S.; Yoshida, K. (Dyes Pigm., 2008)

(untitled) - Ooyama, Y.; Nagano, S.; Okamura, M.; Yoshida, K. (Eur. J. Org. Chem., 2008)

(untitled) - Yoshida, K.; Matsuoka, M.; Yamashita, Y.; Kitao, T. (Bull. Chem. Soc. Jpn., 1980)

(untitled) - Katsuhira, Y.; Miwa, I.; Hiroyuki, H.; Mayumi, Y.; Yuji, K. (Bull. Chem. Soc. Jpn., 1988)

(untitled) - Yoshida, K.; Yamamoto, M.; Ishiguro, M. (Chem. Lett., 1986)

(untitled) - Yoshida, K.; Koujiri, T.; Oga, N.; Ishiguro, M.; Kubo, Y. (J. Chem. Soc., Chem. Commun., 1989)

U.S. Patent - Rickwood, M.; Marsden, S. D.; Askew, V. E. (Photochromic spiroxazine compounds, 1995)

(untitled) - Tathe, A. B.; Sekar, N. (J. Fluoresc., 2015)

(untitled) - Ooyama, Y.; Nabeshima, S.; Mamura, T.; Ooyama, H. E.; Yoshida, K. (Tetrahedron, 2010)

(untitled) - Gates, M.; Newhall, W. F. (J. Am. Chem. Soc., 1948)

(untitled) - Land, E. J.; Ramsden, C. A.; Riley, P. A.; Yoganathan, G. (Tetrahedron, 2003)

(untitled) - Villemin, D.; Benabdallah, M.; Choukchou-Braham, N.; Mostefa-Kara, B. (Synth. Commun., 2010)

(untitled) - Villemin, D.; Benabdallah, M.; Rahmoun, N.; Jouannic, C.; Choukchou-Braham, N.; Mostefa-Kara, B. (Synth. Commun., 2010)